Hidden burden of chikungunya in North India; A prospective study in a tertiary care centre - Anju Dinkar; Jitendra Singh; Pradyot Prakash; Arghya Das; Gopal Nath (Elsevier, 2018)
Background: Arboviral diseases, such as chikungunya, dengue and now zika represent a public health problem, especially in tropical countries. Epidemiology of chikungunya and dengue is well known, including its social and climatic factors associated, but only few data and reports of chikungunya are available from North India. The clinical differentiation of chikungunya from dengue is no doubt challenging since both diseases can share clinical signs and symptoms leading to potential misdiagnosis of chikungunya in areas where dengue is endemic. The aim of this study was to know the seroprevalence, seasonal trends, clinical presentations of chikungunya and its co-infection with dengue virus. Methods: This was a prospective study conducted in Varanasi, from January to December 2016. All serum samples were tested for both chikungunya and dengue IgM antibodies by MAC ELISA test. Results: Total of 186 samples, out of which 108 (58%) samples were total seropositive, 23 (12.37%) samples positive for chikungunya IgM antibodies, 57 (30.65%) samples positive for dengue and 28 (15.05%) samples positive for both chikungunya and dengue. The most affected age group was 20-30 years and males were more affected than females. A seasonal peak for chikungunya and its co-infection with dengue were seen in November. Conclusion: In India, the seroprevalence of chikungunya is increasing. India is a rapidly developing country where adequate sanitation is required. More aggressive intervention and vigilance by health authorities is needed to decrease vector born diseases. Keywords: Chikungunya, Dengue haemorrhagic fever, Co-infection, Vector borne diseases, Joint pain